Developing The Mathematics Conceptual Understanding and Procedural Fluency through Didactical Anticipatory Approach Equipped with Teaching AIDS - Asmida Asmida; Sugiatno Sugiatno; Agung Hartoyo (JETL (Journal of Education, Teaching and Learning), 2018)
The students’ conceptual understanding and procedural fluency have not been yet integrated into the mathematics learning as the teachers’ common mathematics textbook has not explicitly explained the conceptual understanding and procedural fluency in solving the mathematical problems that the teachers have not yet connected it to the mathematics learning. The interview result shows that the students only memorize the procedures without understanding. If the procedure is continuously applied, it is predicted that the students may face the epistemological obstacles in solving the mathematical problems. This research aims at developing the students' mathematics conceptual understanding and procedural fluency through the Didactic Anticipatory Approach equipped with the teaching aids in learning the operations of integer multiplication at Junior High School in Grade VIII. This pedagogical action research involves 14 students. The research data are collected using tests, interviews, voice recorders and cameras. The result shows that learning mathematics through the Didactic Anticipatory Approach equipped with teaching aids may develop the students' conceptual understanding and mathematics procedural fluency marked by the reduced students’ epistemological obstacles. However, they are not yet been completely resolved. The students' conceptual understanding and mathematics procedural fluency also supported with the average posttest score higher than that of the pretest score.